2016
DOI: 10.1136/archdischild-2016-311030
|View full text |Cite
|
Sign up to set email alerts
|

Blended foods for tube-fed children: a safe and realistic option? A rapid review of the evidence

Abstract: With the growing number of children and young people with complex care needs or life-limiting conditions, alternative routes for nutrition have been established (such as gastrostomy feeding). The conditions of children and young people who require such feeding are diverse but could relate to problems with swallowing (dysphagia), digestive disorders or neurological/muscular disorders. However, the use of a blended diet as an alternative to prescribed formula feeds for children fed via a gastrostomy is a content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 13 publications
5
68
0
1
Order By: Relevance
“…Although reasons why BTF ameliorates symptoms of tube feeding intolerance in some individuals have not been elucidated, at least part of the answer might be dietary diversity and subsequent microbiome response to whole food feeding. These early research associations are congruent with anecdotal reports from tube‐fed patients and/or caregivers of tube‐fed patients that BTF reduces gastrointestinal problems compared with CF feeding . Furthermore, BTF may be cost‐effective compared with CF by replacing more expensive elemental formulas and/or gastrointestinal medications.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Although reasons why BTF ameliorates symptoms of tube feeding intolerance in some individuals have not been elucidated, at least part of the answer might be dietary diversity and subsequent microbiome response to whole food feeding. These early research associations are congruent with anecdotal reports from tube‐fed patients and/or caregivers of tube‐fed patients that BTF reduces gastrointestinal problems compared with CF feeding . Furthermore, BTF may be cost‐effective compared with CF by replacing more expensive elemental formulas and/or gastrointestinal medications.…”
Section: Discussionsupporting
confidence: 66%
“…In a review of clinical studies, Bobo noted a high variability of BTF composition in several studies, which can impact weight in adults and growth in children. Other studies demonstrated that BTF supports growth goals in children and weight maintenance in adults . Whole food blends are considerably more viscous than CF and may increase tube occlusion .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Destaca-se que esses mesmos pesquisadores reforçam a necessidade da prescrição e do acompanhamento por nutricionista para a utilização de dietas enterais artesanais. 5,[8][9][10][11] Também é verdade que alguns estudos apontam como inseguro e ineficaz o uso das fórmulas artesanais, no entanto, alguns deles foram financiados por laboratórios que produzem fórmulas industrializadas. 12,13 Pesquisadores apontam que o lobby das indústrias de medicamentos e fórmulas nutricionais é o principal fator para a judicialização da saúde devido a sua influência junto às associações, entidades de classe e profissionais de saúde, que faz com que usuários e prescritores passem a considerar imprescindível o uso de determinada fórmula nutricional.…”
Section: Contextualização Da Experiênciaunclassified